The safety and efficacy of daylight photodynamic therapy in the treatment of actinic keratoses: a systematic review and meta‐analysis. (9th September 2018) - Zhao, Weijia; Guan, Meng; Nong, Xiang; Li, Qian; Chen, Zonghan
Abstract: Daylight photodynamic therapy (DLPDT) is a novel therapeutic approach for actinic keratoses (AKs). This study aimed to evaluate the safety and efficacy of DLPDT in treating patients with AKs as compared to conventional photodynamic therapy (CPDT). PubMed, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials were searched for relevant randomized controlled trials (RCTs) published before November 2017, based on the following search terms: "solar keratoses", "actinic keratoses", "photodynamic therapy", "daylight photodynamic therapy", "conventional photodynamic therapy", and "randomized". The complete response rate, patient satisfaction, and patient‐reported pain after intervention with DLPDT or CPDT were primarily measured. Sensitivity analysis was conducted to determine the reliability of results. Begg's and Egger's tests were used to assess the likelihood of publication bias. Eight RCTs, comprising a total of 424 patients with AKs treated with DLPDT or CPDT, were included. No significant difference was found between the lesion response rate and the mean lesion response in a comparison of DLPDT and CPDT treatments. Generally, DLPDT was associated with higher patient satisfaction than CPDT. The patients who underwent DLPDT experienced less pain than those who underwent CPDT. Most of our results were of high stability and low sensitivity. Meanwhile, no statistical evidence of publication bias among studies was found under all comparisons. In conclusion, DLPDT is a safe and effective therapy, which could help in selecting the most appropriate therapeutic method for treating AKs and in guiding physicians to optimize treatment strategies.